HUKUM ISLAM DAN MORALITAS DALAM MASYARAKAT MADANI - Ihsan, Muhammad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2012)
This paper intends to provide confirmation of the role of Islamic law in the realization of civil society through the revitalization of ethical values. This descriptive thought was very important if it is associated with the condition of the country was entering a period of transition from the new order to the reform period. Extreme changes in the political situation has triggered individuals and groups in t his country rebuild their identity and orientation of their lives, without exception Muslim groups. Muslims are very excited to welcome this momentum to bring back the ideals of civil society through Islamic law. Islamic law has the main goal to achieve and improv e human morality. The Islamic law has commitent to realize the ethics and morality of mankind through the formulation of rules that come with punitive sanctions. This effort became one of the methods and approaches to Islamic law, so that the moral valuesshared by everyone. If people adhere to the values of morality, then at the same time ci vil society will be realized.***Tulisan ini bermaksud memberikan penegasan terhadap peran hukum Islam dalam mewujudkan masyarakat madani (civil society ) melalui revitalisasi nilai-nilai etika. Pemikiran deskriptif ini terasa sangat penting jikadikaitkan dengan kondisi bangsa yang tengah memasuki masa transisi dari masa orde baru m enuju masa reformasi. Perubahan situasi politik secara ekstrim telah memicu setiap individu dan kelompok di negara ini menata kembali identitas diri dan orientasi hidup mereka, tanpa terkecuali kelompok Muslim. Umat Islam sangat antusias menyambut momentum ini untuk mewujudkan kembali cita-cita masyarakat madani melalui hukum Islam. Hukum Islam memiliki tujuan utama untuk mewujudkan dan memperbaiki moralitas manusia. Komitmen hukum Islam dalam mewujudkan etika dan moralitas ummat adalah melalui perumusan peraturan yang dilengkapi dengan sanksi hukuman. Upaya ini menjadi salah satu metode dan pendekatan oleh hukum Islam, sehing ga nilai-nilai moralitas dimiliki oleh semua orang. Jika masyarakat mematuhi nilai-nilai moralitas, maka pada saat yang sama masyarakat sipil ( civil society ) akan terwujud.***Keywords: Hukum Islam, moralitas, masyarakat madani, peradaban